Chicken soup for little souls. The Braids girl - McCourt, Lisa.; Ladwig, Tim; Hansen, Mark Victor; Canfield, Jack, 1944- (Deerfield Beach, FL. : Health Communications, 1998)
While helping Grandpa Mike do volunteer work at a shelter for less fortunate people, Izzy tries to figure out the best way to help a girl her own age who is staying there.
"Based on the ... best-selling series Chicken soup for the soul by Jack Canfield and Mark Victor Hansen."
Keywords: Homeless persons -- Fiction; Poverty -- Fiction; Voluntarism -- Fiction; Friendship -- Fiction